2015
DOI: 10.5152/tjg.2015.4642
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of colonoscopy findings in a Chinese and American tertiary hospital

Abstract: Background/Aims: To compare the colonoscopy findings of a tertiary Chinese hospital with those of an American tertiary hospital. Materials and Methods: Hundred consecutive colonoscopies performed in August 2008 at the First Affiliated Hospital of Nanchang University in China and at the Emory University Hospital, United States of America, were investigated. The endoscopic findings and the histopathology results were statistically compared. Results: The average age of Chinese patients who underwent colonoscopy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Chronic diarrhoea and chronic abdominal pain are two common indications for undergoing colonoscopy in this study whereas, rectal bleeding, chronic diarrhea and chronic abdominal pain were common indication for colonoscopy in other studies by Ngimet al [9], Osinowo A [10], Salamat A [6],Plummer et al [12]. But in the study done in Chinese and American tertiary hospital by Wang et al [14] the commonest indication was screening for colorectal carcinoma. This finding gives a clue that developing country like ours are still focusing on treatment rather than preventive medicine.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Chronic diarrhoea and chronic abdominal pain are two common indications for undergoing colonoscopy in this study whereas, rectal bleeding, chronic diarrhea and chronic abdominal pain were common indication for colonoscopy in other studies by Ngimet al [9], Osinowo A [10], Salamat A [6],Plummer et al [12]. But in the study done in Chinese and American tertiary hospital by Wang et al [14] the commonest indication was screening for colorectal carcinoma. This finding gives a clue that developing country like ours are still focusing on treatment rather than preventive medicine.…”
Section: Discussionmentioning
confidence: 51%
“…Haemorroid was common finding in other studies done in African countries [8,10,12]. In comparative study done in China and USA by Wang H [14] common finding was polyps both in China and USA followed by colitis.In the study done in Rawalpindi [4], inflammatory bowel disease was dominant colonoscopy finding.…”
Section: Discussionmentioning
confidence: 83%
“…Rectal bleeding, chronic diarrhea and chronic abdominal pain were common indication for colonoscopy in studies by Salamat et al, 8, Ngimet al, 10 Osinowo et al, 13 and Plummer et al, 16 In a study by Wang et al, 17 in a tertiary hospital in America, the commonest indication was screening for colorectal polyp and carcinoma. The most common indication was bleeding per rectum and was observed in 37.9% patients in the study by Dinesh et al, 9 in India.…”
Section: Resultsmentioning
confidence: 96%
“…Similar were the findings in the Nepalese study by Shrestha et al 11 Chronic diarrhea and chronic abdominal pain were two common indications for undergoing colonoscopy in the study by Shrestha et al 11 Unlike the study in America, where screening colonoscopy was the commonest indication , this was the least common indication in our present study. In comparative study done in China and USA by Wang et al 17 common finding were polyps both in China and USA followed by colitis. In the study in Pakistan by Salamat et al, 8 inflammatory bowel disease was dominant colonoscopy finding.…”
Section: Resultsmentioning
confidence: 97%
“…Comparative study between American and Chinese population showed mean age of Chinese population to be 45 years. (7)The similar change in trend has also been noted in age of CRC in Asian countries versus western world where it is considered to be a disease of old age with onset from 50 to 70 years. While in Pakistan young onset CRC is at rise with mean age of CRC to be 45.…”
Section: Discussionmentioning
confidence: 59%